Revealing the diversity and complexity behind long-term income inequality in Latin America, 1920-2011 - Pablo Astorga (European Historical Economics Society (EHES), 2024)
This paper analyses and documents new long-term income inequality series for Argentina, Brazil, Chile, Colombia, Mexico and Venezuela based on dynamic social tables with four occupational groups. This enables the calculation of comparable Overall (4 groups) and Labor Ginis (3 groups) with their between- and within-groups components. The main findings are: the absence of a unique inequality pattern over time; country outcomes characterized by trajectory diversity and level divergence during industrialization, and by commonality and convergence post 1980; the occurrence of inequality-levelling episodes with different timing and length; and significant changes in trends, but also evidence indicating persistence.
Keywords: O10; N1; O15; O54; 330; economic development; industrialisation; income inequality; LatinAmerica